Systemic risk in the major Eurobanking markets: evidence from inter-bank offered rates - Simpson, John; Evans, John (Elsevier BV, North-Holland, 2005)
In Eurobanking, the London Interbank Offered Rate is often assumed to be the reference rate for Eurocurrency loan transactions. A debate continues as to whether or not dominance by London is evident through the movements in interbank offered rates and whether any adverse shocks experienced there are felt through the other major Eurobanking centres of New York and Tokyo. This study finds that in the longer-term New York is the driver of both the London and the Tokyo interbank lending rates. The more important issue is that the interbank offered rates in London, New York and Tokyo show a long-term cointegrating relationship. Whilst Western banking is incestuous in terms of interbank lines of credit, support is nevertheless provided for rational expectations and market efficiency. However, cointegration also constitutes interdependence and in turn shows evidence of systemic risk (the threat of contagion) in these centres is provided. The implications for future research into global financial stability are alluded to in the conclusion.